Nociceptive Local Field Potentials Recorded from the Human Insula Are Not Specific for Nociception - Liberati, Giulia; Klöcker, Anne; Safronova, Marta M.; Ferrão Santos, Susana; Ribeiro Vaz, Jose-Geraldo; Raftopoulos, Christian; Mouraux, André (PLOS Biology, 2016)
Local field potentials elicited in the human insular cortex by painful stimuli reflect cortical activity that is unrelated to pain perception and so cannot be used as an objective measure of pain.